SOLITARY CIRCUMSCRIBED "PEARL WHITE" RETINAL MASS (SO-CALLED RETINAL ASTROCYTIC PROLIFERATION) RESIDES IN DEEP RETINA OR BENEATH RETINA: FINDINGS ON MULTIMODAL IMAGING IN 4 CASES. Issue Volume 11:Issues 1(2017:Winter) (2017) - Shields, Carol L.; Roe, Richard; Yannuzzi, Lawrence A.; Shields, Jerry A.
Abstract : Four cases of solitary circumscribed retinal astrocytic proliferation were evaluated with multimodal imaging and this avascular "pearl white" lesion appears to arise in the deep retina or retinal pigment epithelium and not in the nerve fiber layer, as originally suspected. Abstract : Purpose: To report novel observations of previously described solitary circumscribed retinal astrocytic proliferation using spectral domain optical coherence tomography that suggests this tumor does not arise in the nerve fiber layer as initially believed, but arises within deep retinal or retinal pigment epithelial structures. Methods: Retrospective review of four cases. Results: Patient age ranged from 46 to 75 years. The tumor was pearl white or yellow-white (n = 4, 100%), located in the macula (n = 1, 25%) or macula to equator (n = 3, 75%) regions, and with mean tumor base of 1.2 mm and thickness of 0.8 mm. There were no feeding vessels, intrinsic vessels, subretinal fluid, or vitreoretinal traction. Mild surrounding retinal pigment epithelial hyperplasia and atrophy rimmed each tumor (n = 4, 100%). Fluorescein angiography depicted the mass with early hypofluorescence (n = 3/3, 100%) and late hypofluorescence (n = 2/3, 67%). Spectral domain optical coherence tomography demonstrated the mass with an abruptly elevated "snowball" configuration (n = 4, 100%), with smooth or slightly irregular surface (n = 4, 100%), and originating from deep retina or retinal pigment epithelial (n = 4, 100%), with overlying compression and draping of retinal tissue (n = 4, 100%). Conclusion: This previously described small yellow-white retinal tumor appears to arise in the outer retinal layers and not from the inner retinal layers as formerly believed. This tumor may not be astrocytic as initially believed since it arises deep within the retina, but it could represent a deep glial or pigment epithelial fibrous mass. The pathogenesis and pathology of this rare lesion remain unknown.